2021
DOI: 10.3390/ijgi10080528
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Impact of Large Data Imports in OpenStreetMap

Abstract: OpenStreetMap (OSM) is a global mapping project which generates free geographical information through a community of volunteers. OSM is used in a variety of applications and for research purposes. However, it is also possible to import external data sets to OpenStreetMap. The opinions about these data imports are divergent among researchers and contributors, and the subject is constantly discussed. The question of whether importing data, especially large quantities, is adding value to OSM or compromising the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…For some places, the building footprints in OSM might already come from an imported dataset, but they need to be accepted by a human-in-the-loop process, for instance using the mapwith.ai editor 48 or similar tools. A large direct import of Microsoft building data into OSM seems unlikely at the moment, however, it has been shown for the road network that imports can increase contributor activity especially for already engaged mappers and an interplay of data imports and updates by contributors could improve OSM data significantly 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…For some places, the building footprints in OSM might already come from an imported dataset, but they need to be accepted by a human-in-the-loop process, for instance using the mapwith.ai editor 48 or similar tools. A large direct import of Microsoft building data into OSM seems unlikely at the moment, however, it has been shown for the road network that imports can increase contributor activity especially for already engaged mappers and an interplay of data imports and updates by contributors could improve OSM data significantly 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, two lines of effort have emerged -ameliorating the data and assessing their quality. Both often require a reference dataset, another instance of assumedly sufficient reliability that can be freely used to either ingest it in OSM or use it to cross-check the content of OSM (Zielstra et al 2013;Zheng & Zheng 2014;Brovelli et al 2016;Juhász & Hochmair 2018;Zhou 2018;Witt et al 2021;Majic et al 2021). The same concepts apply for other instances beyond OSM.…”
Section: Openstreetmap and Quality Controlmentioning
confidence: 99%
“…Similar results were found in Grchenig et al (2014), and even more, the authors mentioned that the imported data had a negative influence on the OSM community. On the contrary, a recent study showed that contributor activity increased after a massive import (Witt et al, 2021). The question of how OSM ecosystem changes and will change, as the community of contributor expands to include industries or professional data producers, and massive external data co-exist with individual contributions in the databases, has been deeply studied in Hayat (2019).…”
Section: Related Workmentioning
confidence: 99%
“…We saw that recent research allows to study the influence of massive imports on OSM community behavior. To the best of the authors' knowledge, few researches focused on the evolution of massive imports over time in term (Witt et al, 2021). Our paper contributes to this gap by proposing an approach to identify types of modifications and evolution patterns.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation